answer this question fast
Attachments:
![](https://hi-static.z-dn.net/files/d61/4766f6ba9c10b1c5384b362bc185e897.jpg)
Answers
Answered by
0
please find the attachment
Attachments:
![](https://hi-static.z-dn.net/files/de5/dffe2e5fca1ae54c539a2ef573c3a8c7.jpg)
Answered by
0
At first using quadratic formula.....get the roots !
Then by α + β = -b/a where
α + β = -coefficient of x/ coefficient of x^2
And
αβ = c/a where
αβ = constant term /coefficient of x^2
Substitute all the values in these following steps !!!!
:-)
Similar questions